2010
DOI: 10.1007/s10344-010-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a serological surveillance protocol for rabbit hemorrhagic disease by combining mathematical models and field data: implication for rabbit conservation

Abstract: Rabbit hemorrhagic disease (RHD) became endemic in wild rabbit populations in the Iberian Peninsula after its first arrival in 1988. This had significant implications for both the economy and environmental conservation because rabbits are one of the main game species in the Iberian Peninsula and a keystone species in the Mediterranean ecosystems. As a consequence it is planned to include RHD surveillance in the Spanish Wildlife Disease Surveillance Strategy. Nevertheless, there is no practical methodology incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…) is poorly understood (but see Calvete , Cotilla et al. ). Furthermore, the roles of predation and hunting in rabbit population dynamics in conflict areas have not been investigated, and the potential differences in their effects on the two rabbit subspecies are not understood.…”
Section: Ecological Economic and Social Factors Involved In The Confmentioning
confidence: 99%
“…) is poorly understood (but see Calvete , Cotilla et al. ). Furthermore, the roles of predation and hunting in rabbit population dynamics in conflict areas have not been investigated, and the potential differences in their effects on the two rabbit subspecies are not understood.…”
Section: Ecological Economic and Social Factors Involved In The Confmentioning
confidence: 99%
“…An Iberian Wildlife Disease Surveillance Strategy could be designed in order to monitor the impact and evolution of viral diseases on rabbit populations. Cotilla and colleagues [76] recently proposed a protocol, to be included in the Spanish Wildlife Disease Surveillance Strategy, for monitoring RHD based on the prevalence of antibodies to this disease and the abundance of rabbits. These authors concluded that managers and conservationists should urgently focus their efforts on rabbit populations with low antibody prevalence against RHD, and base their strategies on tested management measures that ensure an increase in abundance allowing rabbits to overcome the suppressive impact of this disease [76].…”
Section: Disease Controlmentioning
confidence: 99%
“…Third, the effect of concomitant diseases may exacerbate what would otherwise be an asymptomatic mange infection (Balestrieri et al, 2006). For example, wild rabbit populations are known to suffer from periodical outbreaks of myxomatosis and RHD with mortality rates varying between years and places (Calvete et al, 2002;Cotilla et al, 2010) that may be related with mange outbreaks. In fact, we found an association between the presence of antibodies to S. scabiei and to myxoma virus.…”
Section: Discussionmentioning
confidence: 99%